The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1093/jn/136.5.1409s
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Experience-Based Measure of Household Food Insecurity within and across Seasons in Northern Burkina Faso

Abstract: Organizations measure household food insecurity for program design, planning, targeting, implementation, monitoring, and evaluation, but existing measures often are inadequate. Qualitative and quantitative methods were used to develop and validate an experienced-based measure of the access component of food insecurity in northern Burkina Faso. In-depth interviews on food insecurity were done with 10 household heads and 26 women using interview guides. We identified themes, classified households, created a tabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
141
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(150 citation statements)
references
References 12 publications
5
141
0
4
Order By: Relevance
“…35 The HFIAS was initially developed by Food and Nutrition Technical Assistance (FANTA) project based on validation studies in eight countries including the US. 44,45 Validation studies have demonstrated that the HFIAS distinguishes food-secure from -insecure individuals or households across different cultural contexts. The questions cover three domains of the experience of food insecurity: (1) anxiety and uncertainty about food supply, (2) insufficient quality and variety of food, and (3) insufficient food intake and its physical consequences.…”
Section: Methodsmentioning
confidence: 99%
“…35 The HFIAS was initially developed by Food and Nutrition Technical Assistance (FANTA) project based on validation studies in eight countries including the US. 44,45 Validation studies have demonstrated that the HFIAS distinguishes food-secure from -insecure individuals or households across different cultural contexts. The questions cover three domains of the experience of food insecurity: (1) anxiety and uncertainty about food supply, (2) insufficient quality and variety of food, and (3) insufficient food intake and its physical consequences.…”
Section: Methodsmentioning
confidence: 99%
“…Household level food insecurity is measured with a six item scale that was adapted from published food insecurity scales used in developing countries (Coates, Frongillo, Rogers, Webb, Wilde, & Houser, 2006;Frongillo & Nanama, 2006;Melgar-Quinonez, et al, 2006;. The items were included after much discussion with the interviewing team and pilot testing and reflect what appear to be universal expressions of food insecurity .…”
Section: Measuring Household Food Insecuritymentioning
confidence: 99%
“…These studies use food insecurity scales which capture several dimensions of food insecurity including worry over the adequacy of the food supply, concern about the quality of the food supply, and changes in eating patterns in response to food shortages. Results from a number of developing country studies indicate that these qualitative self-assessments provide valid indicators of food insecurity (Frongillo & Nanama, 2006;Melgar-Quinonez, Zubieta, MkNelly, Nteziyaremye, Gerardo, & Dunford, 2006;.…”
Section: Introductionmentioning
confidence: 99%
“…In developing a tool to measure household food insecurity across countries and cultures, researchers have most often either adapted a version of the Cornell/Radimer measuring tool, which was initially developed for use in the USA, or developed a tool based on research on how households experience food insecurity in various countries and geographical areas (5) . Both methods have produced valid or accurate measurements (6)(7)(8) .…”
mentioning
confidence: 99%